Antigen and Cell-Based Assays for the Detection of Non-HLA Antibodies - Lammerts, Rosa G. M.; Altulea, Dania; Hepkema, Bouke G.; Sanders, Jan-Stephan; Born, Jacob van den; Berger, Stefan P. (Frontiers in Immunology, 2022)
To date human leukocyte antigens (HLA) have been the major focus in the approach to acute and chronic antibody mediated rejection (AMBR) in solid organ transplantation. However, evidence from the clinic and published studies have shown that non-HLA antibodies; particularly anti-endothelial cells antibodies (AECA), are also mediators of ABMR either independently, or synergistically in the presence of donor specific anti-HLA antibodies (DSA). Numerous studies have explored the influence of AECA on clinical outcomes, yet the determination of the exact clinical relevance of non-HLA antibodies in organ transplantation is not fully established. This is due to highly heterogenic study designs including differences in testing methods and outcome measures. Efforts to develop reliable and sensitive diagnostic non-HLA antibody tests are continuously made. This is essential, considering the technical difficulties of non-HLA antibody assays and the large variation in reported incidences of antibodies. In addition, it is important to take donor-specificity into account in order to draw clinically relevant conclusions from non-HLA antibody assays. Here, we provide an overview of non-HLA solid-phase and cell-based crossmatch assays for use in solid organ transplantation that are currently available, either in a research setting or commercially.